KINERJA PEGAWAI PADA UNIT PELAYANAN PENDAPATAN DAERAH (UPPD) KANTOR SAMSAT BANJARMASIN II - Muhammad Aulia Ramadani; Muhammad Riduansyah Syafari (Jurnal Administrasi Publik dan Pembanguan, 2019)
Employee performance in a motor vehicle tax payment service is very important. Various efforts to repair and rearrangement have been taken seriously. Even so, the results still do not look encouraging, because there are still many illegal levies, inconsistent with the speed of service, and employee discipline, is still a daily sight. The research method used is a qualitative approach with a qualitative descriptive research type. Using research informants. Data collection techniques are, Observations, Interviews, and Documents. Data Analysis Techniques include Data Reduction, Data Presentation, and Conclusion Withdrawal. The results showed that the Employee Performance in the Regional Revenue Service Unit (UPPD) of the SAMSAT Banjarmasin II Office was still low because there were still officers who could not be replaced directly by anyone if they were not present unless appointed directly by the leadership, some officers were found to practice brokers secretly , and inconsistent with the speed of service. However, in the event that the service process for motor vehicle tax payments has been carried out properly because it is in accordance with the procedures established by the SOP.